2012
DOI: 10.1111/j.1540-8159.2012.03497.x
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ Attitudes and Perceptions of Implantable Cardioverter‐Defibrillators: Potential Barriers to Appropriate Primary Prophylaxis

Abstract: Refusal of ICD is common among primary prevention candidates. Common themes in the decision-making process include insight into personal risk of SCD, and perceived strength of the physician recommendation. Providers may want to consider assessment of patients' individual understanding and perceptions when discussing ICD prophylaxis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 36 publications
3
45
0
2
Order By: Relevance
“…(18) However, to our knowledge, no prior study has replicated these findings in a healthcare setting similar to that in Singapore, which has a unique patient population. As such, the present study, which was conducted in a large-volume centre in Singapore, aimed to determine if demographic and social factors had any correlation with a patients' decision to decline the ICD implant.…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…(18) However, to our knowledge, no prior study has replicated these findings in a healthcare setting similar to that in Singapore, which has a unique patient population. As such, the present study, which was conducted in a large-volume centre in Singapore, aimed to determine if demographic and social factors had any correlation with a patients' decision to decline the ICD implant.…”
Section: Introductionmentioning
confidence: 66%
“…A previous study reported that demographic and social factors were significantly correlated with ICD implantation rates; however, it was conducted in the United States and had a very different population base from that encountered in the authors' local practice. (18) To our knowledge, this was the first attempt to replicate the study in a large-volume centre in Singapore.…”
Section: Discussionmentioning
confidence: 94%
“…Factors involved in refusal include perceived strength of recommendation by the treating physician, fears about malfunction, and unwillingness to have invasive life-prolonging procedures. 28 Provider practice patterns and type of hospital have also been associated with rates of primary ICD implantation. A single-center study showed that ICD implantation rates were higher when a cardiologist or a heart failure specialist was involved in the care of the patient.…”
Section: Discussionmentioning
confidence: 99%
“…, Yuhas et al . ). In addition, recipients can perceive the ICD as frightening and that it restricts everyday life, which may influence acceptance (Sears et al .…”
Section: Introductionmentioning
confidence: 97%